New Institutional Economics: A Bibliometric Analysis and Future Research Directions - Anam, Muhammad Syariful (Indonesian Journal of Economics, Social, and Humanities, 2024)
This study aims to evaluate scientific publications on new institutional economics and provide some suggestions for future research topics. The Scopus database was used to collect data related to journal articles on the theme of new institutional economics, and 784 scientific articles published in 479 reputable journals and written by 1,274 academics were obtained. The analysis tool used in this research is bibliometric analysis with the help of machine learning tools RStudio and VOSviewer. The results of this study show that there are five main research streams based on the data extraction results, and provide three potential research recommendations that can be considered for future research on new institutional economics topics. This research makes a valuable contribution to assessing new institutional economics publications that can benefit academics and policymakers.